A metformin add-on clinical study in multiple sclerosis to evaluate brain remyelination and neurodegeneration (MACSiMiSE-BRAIN): study protocol for a multi-center randomized placebo controlled clinical trial - De Keersmaecker, Anna-Victoria; Van Doninck, Eline; Popescu, Veronica; Willem, Lander; Cambron, Melissa; Laureys, Guy; D’ Haeseleer, Miguel; Bjerke, Maria; Roelant, Ella; Lemmerling, Marc; D’hooghe, Marie Beatrice; Derdelinckx, Judith; et al. (Frontiers in Immunology, 2024)
Introduction: Despite advances in immunomodulatory treatments of multiple sclerosis (MS), patients with non-active progressive multiple sclerosis (PMS) continue to face a significant unmet need. Demyelination, smoldering inflammation and neurodegeneration are important drivers of disability progression that are insufficiently targeted by current treatment approaches. Promising preclinical data support repurposing of metformin for treatment of PMS. The objective of this clinical trial is to evaluate whether metformin, as add-on treatment, is superior to placebo in delaying disease progression in patients with non-active PMS.Methods and analysis: MACSiMiSE-BRAIN is a multi-center two-arm, 1:1 randomized, triple-blind, placebo-controlled clinical trial, conducted at five sites in Belgium. Enrollment of 120 patients with non-active PMS is planned. Each participant will undergo a screening visit with assessment of baseline magnetic resonance imaging (MRI), clinical tests, questionnaires, and a safety laboratory assessment. Following randomization, participants will be assigned to either the treatment (metformin) or placebo group. Subsequently, they will undergo a 96-week follow-up period.The primary outcome is change in walking speed, as measured by the Timed 25-Foot Walk Test, from baseline to 96 weeks. Secondary outcome measures include change in neurological disability (Expanded Disability Status Score), information processing speed (Symbol Digit Modalities Test) and hand function (9-Hole Peg test). Annual brain MRI will be performed to assess evolution in brain volumetry and diffusion metrics. As patients may not progress in all domains, a composite outcome, the Overall Disability Response Score will be additionally evaluated as an exploratory outcome. Other exploratory outcomes will consist of paramagnetic rim lesions, the 2-minute walking test and health economic analyses as well as both patient-and caregiver-reported outcomes like the EQ-5D-5L, the Multiple Sclerosis Impact Scale and the Caregiver Strain Index. disseminated at scientific conferences, in peer-reviewed publications, to patient associations and the general public.